Fucoxanthin Inactivates the PI3K/Akt Signaling Pathway to Mediate Malignant Biological Behaviors of Non-Small Cell Lung Cancer. (26th November 2022) - Fang, Xuehong; Zhu, Yuzhen; Zhang, Taomin; Li, Qian; Fan, Lvhua; Li, Xiaodan; Jiang, Daishun; Lin, Jie; Zou, Liyi; Ren, Jianwei; Huang, Zunnan; Ye, Hua; et al.
Abstract: Although lung cancer treatment strategies have improved in recent years, the 5-year overall survival of non-small cell lung cancer (NSCLC) remains less than 15%. Chemotherapy is considered the most promising option in the comprehensive treatment of NSCLC. Fucoxanthin (FX) is a natural product derived from brown algae and has extensive applications in medicine. Previous studies reported that FX effectively inhibits the growth of NSCLC cells in vitro and in vivo. However, the mechanism underlying the anti-NSCLC effect of FX remains unknown. In this study, NSCLC cell lines and a xenograft nude mouse model were used to examine the anti-NSCLC activities of FX in vitro and in vivo. Network pharmacology analysis and inhibitors or activators of the PI3K/Akt signaling pathway were used to explore the anti-NSCLC mechanisms of FX. The results indicated that FX could inhibit proliferation, migration, and invasion, arrest cell cycle at the G0/G1 phase, and induce apoptosis of NSCLC cells in vitro. Additionally, FX suppressed tumor growth in vivo. The PI3K/Akt signaling pathway was found to be involved in the anti-NSCLC activity of FX. In conclusion, FX inhibits malignant biological behaviors of NSCLC by suppressing the phosphorylation of both PI3K and AKT, and subsequently inactivating PI3K/AKT signaling pathway.